the answer of this inequality is
A. x<2
6 because you set them equal and solve
Answer:
6 times 3 times 4
18 times 4
= 72
Step-by-step explanation:
hope this helps good luck
Answer:
Step-by-step explanation:
as given in question that a > 0 so
if we put a=1
we get g(x) = f(x)
now put a =2
we get
g(x) = 2 f(x)
here we can see that g(x) would always be greater than or equals to f(x)
so we can say that the graph of g(x) will never be narrower than graph of g(x)
Substitute in the -3
7-2(-3)
According to PEMDAS (parentheses, exponents, multiply, divide, add, subtract ) you must multiply, and then subtract.
7- (-6)
7 + 6= 13
Answer is 13